A Comprehensive Study on Specifying an Intelligent Approach to Solve Network Reconfiguration Problem - Mahmoud Reza Shakarami; Sina Khajeh Ahmad Attari; Farhad Namdari (Institute of Advanced Engineering and Science, 2016)
This paper presents an approach based on biogeography-based optimization (BBO) algorithm to solve the distribution network reconfiguration (DNR) problem for minimizing active power loss. Also it is demonstrated that with considering the nature of reconfiguration problem, among the intelligent algorithms, BBO approach could result the best performance. One of the remarkable advantages of this study is comparing seven different intelligent algorithms in solving network reconfiguration problem. This comparison, not only includes final fitness in optimization process, but also considers number of function evaluation (NFE). The effectiveness of the BBO method has been tested on two different distribution systems and the obtained simulation results are compared with Genetic algorithm (GA), Particle swarm optimization (PSO), Artificial bee colony (ABC), Gravitational search algorithm (GSA), Technical learning based optimization (TLBO) and Cuckoo algorithm (CA). The comparison results show that BBO approach can be an efficient and promising method for solving DNR problems.